ANALISIS PERBANDINGAN EFEKTIVITAS METODE KONVENSIONAL DAN BIM AUTODESK REVIT DALAM PERENCANAAN KONSTRUKSI GEDUNG - Putu Aryastana; I Wayan Gde Erick Triswandana; Putu Agus Sepiantara (Matriks Teknik Sipil, 2025)
Building Information Modeling (BIM) provides a significant improvement in efficiency, accuracy, and coordination compared to conventional 2D-based methods in construction planning and cost estimation. This study employs a descriptive quantitative approach with a comparative method to analyze the effectiveness of conventional and BIM-based methods using Autodesk Revit software in preparing the Quantity Take Off (QTO), Bill of Quantity (BOQ), and Cost Budget Plan (RAB) for the Kerobokan Traditional Village Office Building project in Bali. The secondary data include architectural, structural, and utility design drawings, as well as the 2022 Work Unit Price Analysis (AHSP). The findings indicate that the implementation of BIM reduces project preparation time by 37.72% compared to the conventional method. Furthermore, volume discrepancies were found in concrete work (11.63%), formwork (-5.99%), and reinforcement (36.26%) due to differences in modeling and measurement principles. These results highlight BIM’s crucial role in enhancing estimation accuracy, time efficiency, and design adaptability, particularly in government building projects that must comply with the Ministry of Public Works Regulation No. 22 of 2018 on Cost Budgeting Guidelines.Keywords: autodesk Revit; BIM; BOQ; cost estimation; QTO.